Topographic Constraints on Deviatoric Stress Field in the Indo-Eurasian Collision Region: Seismo-Tectonic Implications - Shrivastava, Mahesh N.; Reddy, C.D.; Prajapati, Sanjay K. (My University, 2013)
The deviatoric stress field are computed from the inversion of Gravitational Potential Energy (GPE) for the Indo-Eurasian plate collision region including the Himalaya and the Tibet Plateau. The resulting stress pattern in combination with stress and strain rates obtained by inverting, respectively, the focal mechanism solution of large earthquakes and GPS derived plate motions are used to study the nature of the present-day deformations. A narrow belt bordering the Himalayan collision zone from the south is characterized by strong compressive stresses. The variations in stress pattern along this belt coincide with arc-normal ridges extending into the Himalaya and are able to explain arc-parallel segmentation of seismicity. Gravitational collapse seems to play an important role in the southeastern Tibet Plateau. Depth sensitivity of the seismic derived stresses and GPS derived surface strain rates coupled with evidence of arcuate shaped high electrical conductivity favour strong ductile flow around the Eastern Himalaya Syntaxis (EHS) at mid-crustal depth. The deflection of crustal flow indicted by the viscous resistance offered by the rigid Sichuan basin adds to the traction stresses to cause clockwise rotation of the block around EHS.
Keywords: Topography; Indo-Eurasia collision; Deviatoric stress; Gravitational potential energy; Eastern Himalaya syntaxis; GPE; GPS; EHS